Topical antifungal keratitis therapeutic potential of Clitoria ternatea Linn. flower extract: phytochemical profiling, in silico modelling, and in vitro biological activity assessment - Yolin Angel, Poomany Arul Soundara Rajan; Jeyakumar, Palanisamy; Jasmin Suriya, Arul Raj; Sheena, Aliyas; Karuppiah, Ponmurugan; Periyasami, Govindasami; Stalin, Antony; Murugan, Kasi (Frontiers in Microbiology, 2024)
Introduction Fungal keratitis (FK) poses a severe threat to vision, potentially leading to blindness if not promptly addressed. Clitoria ternatea flower extracts have a history of use in Ayurvedic and Indian traditional medicines, particularly for treating eye ailments. This study investigates the antifungal and antibiofilm effects of Clitoria ternatea flower extracts on the FK clinical isolate Coniochaeta hoffmannii. Structural details and key compound identification were analysed through FTIR and GC-MS. Methods The minimum inhibitory concentration (MIC) and minimum fungicidal concentration (MFC) of Clitoria ternatea flower extracts were determined using broth dilution and well plate techniques. Biofilm inhibitory activity was assessed through microscopic evaluation, while anti-irritant and cytotoxic properties were evaluated using CAE-EI and MTT assays. Through GC-MS and FT-IR analysis the compounds dissolved in the extract and their functional group were studied, and their toxicity screening and pharmacokinetic prediction were conducted in silico. Subsequently, compounds with high corneal permeability were further identified, and molecular docking and simulation studies at 150 ns were used to investigate their interactions with fungal virulence factors and human inflammatory proteins. Results and Discussion At a concentration of 250 µg/mL, the Clitoria ternatea flower extract displayed effective biofilm inhibition. MIC and MFC values were determined as 500 and 1000 µg/mL, respectively. CAE-EI and MTT assays indicated no significant irritant and cytotoxic effects up to a concentration of 3 mg/mL. Compounds like 9,9-dimethoxybicyclo[3.3.1]nonane-2,4-dione showed high corneal permeability with strong and stable interactions with fungal virulence cellobiose dehydrogenase, endo β 1,4 xylanase, and glucanase, as well as corneal inflammation-associated human TNF-α and Interleukin IL-1b protein targets. The findings indicate that extracts from C. ternatea flowers could be formulated for an effective and safe alternative for developing new topical FK therapeutics.